Impact of geopolitical risk on the information technology, communication services and consumer staples sectors of the S&P 500 Index - Gerard Atabong Fossung; Vasileios Chatzis Vovas; A. M. M. Shahiduzzaman Quoreshi (Journal of Risk and Financial Management, 2021)
We investigate the effect of geopolitical risk on the returns of firms in the Information Technology, Communication Services, and Consumer Staples sectors within the S&P 500 index. We use the event study methodology and perform more than 17,000 regressions to provide empirical evidence at sector level that geopolitical risk leads to different responses across these three sectors. The response of the Information Technology sector is negative for all event windows under study, except the one spanning 10 days prior to the geopolitical event and 10 days after. The Communication Services sector has positive returns as a result of geopolitical events for all event windows, except the one from the geopolitical event date and 5 days after. The Consumer Staples sector shows a negative impact on geopolitical risk for all event windows except the one from the geopolitical event date and 5 days after, demonstrating a negative correlation to the Communication Services sector.
Keywords: 330; geopolitical risk; event study; S&P 500 index; information technology; communication services; consumer staples